Grasping Spatial Relationships: Failure to Demonstrate Allocentric Visual Coding in a Patient with Visual Form Agnosia - Dijkerman, H.Chris; Milner, A.David; Carey, David P. (Consciousness and cognition, 1998)
The cortical visual mechanisms involved in processing spatial relationships remain subject to debate. According to one current view, the “dorsal stream” of visual areas, emanating from primary visual cortex and culminating in the posterior parietal cortex, mediates this aspect of visual processing. More recently, others have argued that while the dorsal stream provides egocentric coding of visual location for motor control, the separate “ventral” stream is needed for allocentric spatial coding. We have assessed the visual form agnosic patient DF, whose lesion mainly affects the ventral stream, on a prehension task requiring allocentric spatial coding. She was presented with transparent circular disks. Each disk had circular holes cut in it. DF was asked to reach out and grasp the disk by placing her fingers through the holes. The disks either had three holes (for forefinger, middle finger, and thumb) or two holes (for forefinger and thumb). The distance between the forefinger and thumb holes, and the orientation of the line formed by them, were independently varied. DF was quite unable to adjust her grip aperture or her hand orientation in the three-hole task. Although she was able to orient her hand appropriately for the two-hole disks, she still remained unable to adjust her grip aperture to the distance between the holes. These findings are consistent with the idea that allocentric processing of spatial information requires a functioning ventral stream, even when the information is being used to guide a motor response.